Pengembangan Model Permainan King Queen Pembelajaran Senam Lantai Peserta Didik Sekolah Dasar - Naila Elmuna; Agus Darmawan; Ranu Baskora Aji Putra; Dwi Tiga Putri (Indonesian Journal for Physical Education and Sport, 2024)
This present research used research and development (R & D) research methods, the subjects in this research are fourth grade in Elementary School. Data collection was carried out using expert evaluation sheets, student questionnaire sheets, and observation sheets. This finding showed that data analysis and evaluation results from experts with an average of 90% including the "very good" category. The results of small-scale trials reached 89%, including the "very good" category, while the results of large-scale trials achieved results of 91% which met the category. "Very good". The conclusion of this research is that the king queen development game model can be used in gymnastics learning for fourth grade elementary school students, with results reaching the very good category of 90%. The suggestions given by researchers are: 1) King queen game development products can be used as alternative learning models and new innovations that are effective and fun and can be used in elementary schools. 2) For physical education teachers, the hope is to be more creative in choosing game models and to innovate in learning.